(untitled) (Docentes 2.0 Journal, 2025)
With the beginning of university life and its multiple demands, students undergo an adjustment process where they must use academic skills to adapt to the pace of the demands and satisfactorily meet each of them. This research aimed to know the characteristics of study habits among new university students in the Bachelor of Business Administration, Medicine, and Psychology at the Autonomous University of Baja California. The research was based on the positivist paradigm, quantitative approach, and descriptive-transversal type. The sample consisted of 269 higher education students. For data collection, the study habits questionnaire was used. The results obtained identified a prevalence in those skills, such as motivation to study, distinguishing itself as a positive resource about the teaching-learning process, in turn, that skill to consider to develop necessary strategies to improve the distribution of time of newly admitted university students.